Foliage response of young central European oaks to air warming, drought and soil type. (26th September 2012) - Günthardt‐Goerg, M. S.; Kuster, T. M.; Arend, M.; Vollenweider, P.
Abstract: Three Central European oak species, with four provenances each, were experimentally tested in 16 large model ecosystem chambers for their response to passive air warming (AW, ambient +1–2 °C), drought (D, −43 to −60% irrigation) and their combination (AWD) for 3 years on two forest soil types of pH 4 or 7. Throughout the entire experiment, the influence of the different ambient and experimental climates on the oak trees was strong. The morphological traits of the Quercus species were affected in opposing ways in AW and D treatments, with a neutral effect in the AWD treatment. Biochemical parameters and LMA showed low relative plasticity compared to the morphological and growth parameters. The high plasticity in physiologically important parameters of the three species, such as number of intercalary veins or leaf size, indicated good drought acclimation properties. The soil type influenced leaf chlorophyll concentration, C/N and area more than drought, whereas foliage mass was more dependent on drought than on soil type. Through comparison of visible symptom development with the water deficits, a drought tolerance threshold of −1.3 MPa was determined. Although Q. pubescens had xeromorphic leaf characteristics (small leaf size, lower leaf water content, high LMA, pilosity, more chlorophyll, higher C/N) and less response to the treatments than Q. petraea and Q. robur, it suffered more leaf drought injury and shedding of leaves than Q. petraea . However, if foliage mass were used as the criterion for sustainable performance under a future climate, Q. robur would be the most appropriate species.